Solving Radical Equations

Solving Radical Equations

Solving radical equations are required to isolate the radicals or surds to one side of the equations. Then square both sides. Here we have two important checkpoints.

Checkpoint 1 for Solving radical equations

Make sure the whole of both sides is to be squared but not squaring individual terms.
This is what I say,
$$ \large \begin{align} (1+2)^2 &= 3^2 \\
1^2 + 2^2 &\ne 3^2 \end{align} $$

Checkpoint 2 for Solving radical equations

Make sure to check the solutions in the original equation.
$$ \large \begin{aligned} \require{AMSsymbols} \require{color}
\sqrt{x} &= -2 \\
\sqrt{x}^2 &= (-2)^2 &\color{green} \text{squaring both sides} \\
x &= 4 \\
\text{LHS} &= \sqrt{4} &\color{green} \text{check} \\
&= 2 \\
&\ne -2 \\
\text{LHS } &\ne \text{ RHS} \\
\therefore &\text{ no solution}
\end{aligned}
$$
OK, now let’s try to attempt the following questions.

Question 1

Solve \( \sqrt{x+1} = 3 \).

\( \begin{aligned} \require{AMSsymbols} \require{color}
\sqrt{x+1}^2 &= 3^2 &\color{red} \text{square both sides} \\
x+1 &= 9 \\
x &= 8 \\
\text{LHS } &= \sqrt{8+1} &\color{red} \text{check} \\
&= \sqrt{9} \\
&= 3 \\
\text{LHS } &= \text{ RHS} \\
\therefore x &= 3
\end{aligned} \)

Question 2

Solve \( \sqrt{x-1} + 3 = 5 \).

\( \begin{aligned} \require{AMSsymbols} \require{color}
\sqrt{x-1} &= 5-3 \\
\sqrt{x-1} &= 2 \\
\sqrt{x-1}^2 &= 2^2 &\color{red} \text{square both sides} \\
x-1 &= 4 \\
x &= 5 \\
\text{LHS } &= \sqrt{5-1} + 3 &\color{red} \text{check} \\
&= \sqrt{4} + 3 \\
&= 2 + 3 \\
&= 5 \\
\text{LHS } &= \text{ RHS} \\
\therefore x &= 5
\end{aligned} \)

Question 3

Solve \( \sqrt{x+2} + 4 = 1 \).

Note that this question explains why the solutions must be checked for solving radical equations.
\( \begin{aligned} \require{AMSsymbols} \require{color}
\sqrt{x+2} &= 1-4 \\
\sqrt{x+2} &= -3 \\
\sqrt{x+2}^2 &= (-3)^2 &\color{red} \text{square both sides} \\
x+2 &= 9 \\
x &= 7\\
\text{LHS } &= \sqrt{7+2} + 4 &\color{red} \text{check} \\
&= \sqrt{9} + 4 \\
&= 3 + 4 \\
&= 7 \\
&\ne 1\\
\text{LHS } &\ne \text{ RHS} \\
\therefore &\text{ no solution}
\end{aligned} \)

Question 4

Solve \( \sqrt{9x}-5 = \sqrt{4x} \).

\( \begin{aligned} \require{color}
\sqrt{9}\sqrt{x}-5 &= \sqrt{4}\sqrt{x} \\
3\sqrt{x}-5 &= 2\sqrt{x} \\
\sqrt{x} &= 5 \\
\sqrt{x}^2 &= 5^2 &\color{red} \text{square both sides} \\
x &= 25 \\
\text{LHS } &= \sqrt{9 \times 25}-5 &\color{red} \text{check} \\
&= \sqrt{9} \times \sqrt{25}-5 \\
&= 3 \times 5-5 \\
&= 15-5 \\
&= 10 \\
\text{RHS } &= \sqrt{4 \times 25} \\
&= \sqrt{4} \times \sqrt{25} \\
&= 2 \times 5 \\
&= 10 \\
\text{LHS } &= \text{ RHS} \\
\therefore x &= 25
\end{aligned} \)

Question 5

Solve \( \sqrt{2x+1} = x-1 \).

\( \begin{aligned} \require{AMSsymbols} \require{color}
\sqrt{2x+1}^2 &= (x-1)^2 &\color{red} \text{square both sides} \\
2x+1 &= x^2-2x + 1 \\
x^2-4x &= 0 \\
x(x-4) &= 0 \\
x &= 0 \text{ or } 4 \\
\text{check for } x&= 0 \\
\text{LHS } &= \sqrt{2 \times 0 + 1} \\
&= \sqrt{1} \\
&= 1 \\
\text{RHS } &= 0-1 \\
&= -1 \\
\text{LHS } &\ne \text{ RHS for } x = 0 \\
\text{check for } x&= 4 \\
\text{LHS } &= \sqrt{2 \times 4 + 1} \\
&= \sqrt{9} \\
&= 3 \\
\text{RHS } &= 4-1 \\
&= 3 \\
\text{LHS } &= \text{ RHS for } x=4 \\
\therefore x &= 4
\end{aligned} \)

Question 6

Solve \( \sqrt{x+10} = \sqrt{2}(x-5) \).

\( \begin{aligned} \require{AMSsymbols} \require{color} \displaystyle
\sqrt{x+10}^2 &= \sqrt{2}^2(x-5)^2 &\color{red} \text{square both sides} \\
x + 10 &= 2(x^2-10x + 25) \\
x + 10 &= 2x^2-20x + 50 \\
2x^2-21x + 40 &= 0 \\
(2x-5)(x-8) &= 0 \\
x &= \frac{5}{2} \text{ or } 8 \\
\text{check for } x&= \frac{5}{2} \\
\text{LHS } &= \sqrt{\frac{5}{2}+10} \\
&= \sqrt{\frac{25}{2}} \\
&= \frac{5}{\sqrt{2}} \\
&= \frac{5\sqrt{2}}{2} \\
\text{RHS } &= \sqrt{2}\left(\frac{5}{2}-5\right) \\
&= \sqrt{2} \times \frac{-5}{2} \\
&= \frac{-5\sqrt{2}}{2} \\
\text{LHS } &\ne \text{ RHS for } x = \frac{5}{2} \\
\text{check for } x&= 8 \\
\text{LHS } &= \sqrt{8+10} \\
&= \sqrt{18} \\
&= 3\sqrt{2} \\
\text{RHS } &= \sqrt{2}(8-5) \\
&= \sqrt{2} \times 3 \\
&= 3\sqrt{2} \\
\text{LHS } &= \text{ RHS for } x = 8 \\
\therefore x &= 8
\end{aligned} \)

Question 7

Solve \( 3x-\sqrt{x} = 2 \).

\( \begin{aligned} \require{AMSsymbols} \require{color} \displaystyle
3x-2 &= \sqrt{x} \\
(3x-2)^2 &= \sqrt{x}^2 &\color{red} \text{square both sides} \\
9x^2-12x +4 &= x \\
9x^2-13x +4 &= 0 \\
(9x-4)(x-1) &= 0 \\
x &= \frac{4}{9} \text{ or } 1 \\
\text{check for } x &= \frac{4}{9} \\
\text{LHS } &= 3 \times \frac{4}{9}-\sqrt{\frac{4}{9}} \\
&= \frac{4}{3}-\frac{2}{3} \\
&= \frac{2}{3} \\
&\ne 2 \\
\text{LHS } &\ne \text{ RHS for } x = \frac{4}{9} \\
\text{check for } x &= 1 \\
\text{LHS } &= 3 \times 1-\sqrt{1} \\
&= 3-1 \\
&= 2 \\
\text{LHS } &= \text{ RHS for } x = 1 \\
\therefore x &= 1
\end{aligned} \)

Question 8

Solve \( \sqrt{x+1} + \sqrt{2x} = 7 \).

\( \begin{aligned} \require{AMSsymbols} \require{color}
\Big(\sqrt{x+1} + \sqrt{2x}\Big)^2 &= 7^2 &\color{red} \text{square both sides} \\
x+1 + 2\sqrt{x+1}\sqrt{2x} + 2x &= 49 \\
3x+1 + 2\sqrt{2x(x+1)} &= 49 \\
2\sqrt{2x(x+1)} &= 48-3x \\
2^2\sqrt{2x(x+1)}^2 &= (48-3x)^2 &\color{red} \text{square both sides} \\
4 \times 2x(x+1) &= 2304-288x + 9x^2 \\
x^2-296x + 2304 &= 0 \\
(x-8)(x-288) &= 0 \\
x &= 8 \text{ or } 288 \\
\text{check for } x &= 8 \\
\text{LHS } &= \sqrt{8+1} + \sqrt{2 \times 8} \\
&= \sqrt{9} + \sqrt{16} \\
&= 3 + 4 \\
&= 7 \\
\text{LHS } &= \text{ RHS for } x=8 \\
\text{check for } x &= 288 \\
\text{LHS } &= \sqrt{288+1} + \sqrt{2 \times 288} \\
&= \sqrt{289} + \sqrt{576} \\
&= 17 + 24 \\
&= 41 \\
&\ne 7 \\
\text{LHS } &\ne \text{ RHS for } x=288 \\
\therefore x &= 8
\end{aligned} \)

Hope these example questions are useful for you to understand better about solving radical equations.

Question for you

Solve \( \sqrt{x+5} + \sqrt{x-2} = \sqrt{5x-6} \).

Please let us know if you need further help solving this equation. Have fun 🙂

Unlock your full learning potential—download our expertly crafted slide files for free and transform your self-study sessions!

Discover more enlightening videos by visiting our YouTube channel!

 

Algebra Algebraic Fractions Arc Binomial Expansion Capacity Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Product Rule Proof Pythagoras Theorem Quadratic Quadratic Factorise Ratio Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Related Articles

Responses

Your email address will not be published. Required fields are marked *